Prevalence of Trematodes on Red Snapper (Lutjanus argentimaculatus) in Floating Net Cages at Lampung, Indonesia - Sri Subekti, ,-
This study was designed to identify the prevalence of trematodes on red snapper (L. argentimaculatus) in floating net cages at Center for Marine culture, Lampung, South Sumatra, Indonesia. The prevalence of trematodes in floating net cages was 83.33%. Among them H. epinepheli was 26.66%, and there were 50% mixed infestation with two species B.epinepheli and H. epinepheli and the other mixed infestation by three species of trematodes B. epinepheli, N. girellae and H. epinepheli were 6.67%